ANALISIS TINGKAT KERAWANAN BANJIR MENGGUNAKAN SISTEM INFORMASI GEOGRAFI DI SUB DAS TOILI KABUPATEN BANGGAI - Muhammad Adam Suni; Melia Nurulaeni; Agung Dwi Kurniawan (Yayasan Nusantara Hasana Berdikari, 2023)
The geographic information system is an information system about collecting and processing data and conveying information in spatial coordinates, where data collected remotely can be analyzed to obtain information about objects, areas, or phenomena. The purpose of this study was to map the level of flood susceptibility in the Toili sub-watershed using spatial analysis based on Geographic Information Systems (GIS) with scoring and overlay. The research parameters consisted of rainfall, elevation, slope, soil type, land cover/use and distance from the river. This research was conducted in the Toili Sub-watershed, Toili District, Banggai Regency because this area experiences flooding every year. The results showed that the level of flood vulnerability was divided into 5 (five) categories, namely not vulnerable, moderately vulnerable, moderately vulnerable, vulnerable and very vulnerable areas that are very prone to flooding are around the river with an area of ​​408 Ha (3,81%), vulnerable category 3.807,67 Ha (35,58%), slightly vulnerable 6.481,19 Ha (60,57%), moderately vulnerable 0,96 Ha (0,01%), and not vulnerable 2,64 Ha (0,02%). Areas that are in the prone to very flood-prone zone are areas that are at low altitudes and most of the land use is open land without vegetation and close to rivers.